Penerapan Model Pembelajaran Berdiferensiasi Pada Siswa Kelas VIII SMPLB Di Sekolah Khusus (SKH) Insan Mulia Kabupaten Tangerang - Rizka Apriana; Hindun (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Children with special needs are children who have unique characteristics compared to (regular) children. To facilitate learning progress, teachers can apply a differentiated learning model. Differentiated learning is one of the learning models where teachers use a variety of different learning methods according to the characteristics, interests, learning styles, and abilities of students. The purpose of this study is to find out more about differentiated learning and how it is implemented in Class VIII Special Schools. This research uses descriptive qualitative method. The data collection methods used were observation, interview, and note-taking. The data subjects in this research are teachers and students of class VIII of SMPLB Insan Mulia Tangerang Regency. The research location is in Pisangan Jaya village, Tangerang Regency. The result of the learning that has been implemented is the discovery of 3 strategies in differentiated learning, Content Differentiation. Content refers to the curriculum and learning materials; 2. Process Differentiation. How students process ideas and information; 3. Product Differentiation. How students demonstrate what they have learned; 4. Differentiation of Learning environment. Differentiated learning has a positive impact on student engagement and learning outcomes, so students do not struggle with learning